2019
DOI: 10.1111/jcpp.13136
|View full text |Cite
|
Sign up to set email alerts
|

Use of medication for attention‐deficit/hyperactivity disorder and risk of unintentional injuries in children and adolescents with co‐occurring neurodevelopmental disorders

Abstract: Background: Attention-deficit/hyperactivity disorder (ADHD) is often associated with other neurodevelopmental disorders (NDs) and with risky behaviors and adverse health outcomes, including injuries. Treatment with ADHD medication has been associated with reduced risk of injuries. However, it is unknown whether the association is present in individuals with co-occurring NDs. The aim of the present study was to estimate the association between ADHD medication use and unintentional injuries in Sweden in children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Despite their clear limitations [57], observational studies have certain advantages and can helpfully complement RCTs. They importantly often include real-world outcomes, such as criminal convictions [58,59], violent re-offending [60], depression [61], suicidality [62,63], substance misuse [64,65], psychotic disorders and hallucinations in childhood and adolescence [66], childhood injuries [67][68][69], emergency visits [70][71][72], and transport accidents [73], motor vehicle crashes [31], and school performance [74,75]. Further strengths of these studies include their large samples and potential for observation over extended periods.…”
Section: What Can We Conclude From Observational Studies?mentioning
confidence: 99%
“…Despite their clear limitations [57], observational studies have certain advantages and can helpfully complement RCTs. They importantly often include real-world outcomes, such as criminal convictions [58,59], violent re-offending [60], depression [61], suicidality [62,63], substance misuse [64,65], psychotic disorders and hallucinations in childhood and adolescence [66], childhood injuries [67][68][69], emergency visits [70][71][72], and transport accidents [73], motor vehicle crashes [31], and school performance [74,75]. Further strengths of these studies include their large samples and potential for observation over extended periods.…”
Section: What Can We Conclude From Observational Studies?mentioning
confidence: 99%
“…In addition, reducing ADHD symptoms in childhood may also be associated with reduced risk of abuse. Previous studies have suggested that medications for ADHD, such as the psychostimulant methylphenidate (MPH) 25,26 , may lower the risk of physical injury [27][28][29] . This was hypothesized to be due to a reduction of core symptoms of impulsivity, inattentiveness and hyperactivity, which results in a decreased likelihood of involvement in accidents 27 .…”
Section: Resultsmentioning
confidence: 99%
“…Also leveraging the substantial value of Swedish National Registry data, Ghirardi et al (this issue) extend findings on the protective effects of medication use to prevent unintentional injuries in youth with ADHD (Ghirardi et al, ), by demonstrating that this risk‐reducing effect extends to individuals who have co‐occurring neurodevelopmental disorders in addition to ADHD. Using a cohort of more than 9,000 individuals, their results show that the risk for unintentional injuries is reduced significantly during time periods in which youth with ADHD are medicated compared to those times when they are unmedicated, regardless of the presence of co‐occurring neurodevelopmental disorders (e.g., ASD, intellectual disability).…”
mentioning
confidence: 90%